2011
DOI: 10.1007/s11104-011-0747-5
|View full text |Cite
|
Sign up to set email alerts
|

Two biochemical forms of phenanthrene recovered in grassland plants (Lolium perenne L. and Trifolium pratense L.) grown in 3 spiked soils

Abstract: Plant storage is a key component in the global cycling of persistent polycyclic aromatic hydrocarbons (PAHs) and constitutes a crucial step to understand environmental fate of such pollutants. This work aimed at quantifying biochemical forms of phenanthrene (PHE) stored in plants and determining the main parameter between the plant species and the soil characteristics involved in the PHE bioaccumulation. An experiment was conducted in a growth chamber to study the storage of PHE in ryegrass and clover in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Light PAHssuch as phenanthrene and anthraceneare first bound to the root epidermis along the elongation zone, then transmitted through epidermal cells into the root cortex of Zea mais and Triticum aestivum . In Trifolium pratense and Lolium perenne roots, phenanthrene occurs primarily in its free form, suggesting accumulation in the cytoplasm and vacuoles . In contrast, Gao et al have demonstrated that PAHs taken up by arbuscular mycorrhizal roots of L. perenne partition from cell solution into organelles.…”
Section: Uptake Of Atmospheric Pahs By Vascular Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light PAHssuch as phenanthrene and anthraceneare first bound to the root epidermis along the elongation zone, then transmitted through epidermal cells into the root cortex of Zea mais and Triticum aestivum . In Trifolium pratense and Lolium perenne roots, phenanthrene occurs primarily in its free form, suggesting accumulation in the cytoplasm and vacuoles . In contrast, Gao et al have demonstrated that PAHs taken up by arbuscular mycorrhizal roots of L. perenne partition from cell solution into organelles.…”
Section: Uptake Of Atmospheric Pahs By Vascular Plantsmentioning
confidence: 99%
“…When plants are grown in PAH-contaminated soils, PAHs are mainly adsorbed on root surfaces prior to penetrating inner root tissues. ,,, It has been demonstrated that PAHs pass through the cell wall of ryegrass arbuscular mycorrhizal roots . Light PAHssuch as phenanthrene and anthraceneare first bound to the root epidermis along the elongation zone, then transmitted through epidermal cells into the root cortex of Zea mais and Triticum aestivum .…”
Section: Uptake Of Atmospheric Pahs By Vascular Plantsmentioning
confidence: 99%
“…Four plastic pots are placed in the EC around the intake tube (12 cm high × 8 cm diameter). The pots were filled with 300 g dry weight (DW) of agricultural soil from Maconcourt (France) (see Chiapusio et al 29 for characteristics), sieved to 2 mm, to act as simplified microsystems. Each chamber is placed on a PMMA saucer supplying water to the pots, secured by a holder that prevents PHE water contamination.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Soil samples were dried at room temperature (18 °C) under fumehood aspiration and ground with mortar and pestle. This soil drying technique did not provoke any PHE dissipation or volatilization. , Fifty grams of dry soil mixed with diatomaceous earth was put into a 100 mL extraction cell and PHE was extracted twice with an accelerated solvent extractor (ASE 100, Dionex, France) with 60 mL of cyclohexane for 5 min at 100 °C and 100 bar.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation